The Quantification of Chinese Society: Why Did Liang Qichao Ask for Statistics? - Christ, Stefan (Journal of the European Association for Chinese Studies, 2025)
This article seeks to explain the sharply increasing tendency to quantify Chinese society in the twentieth century. It argues that this trend is inherently connected to the passage from a hierarchically stratified society to a one that was more functionally differentiated, which also resulted in the emergence of a new concept of society. The relation between social differentiation and quantification is explored by way of comparing an eighteenth-century essay by Qian Weicheng, which presents a rather typical late imperial vision of social order, with an early twentieth-century article by Liang Qichao, which is one of the earliest texts to lament the lack of numbers and statistics regarding the Chinese population. 本文探討了20世紀中國社會在量化管理方面迅速增長的趨勢及其成因。研究發現，這一趨勢與社會結構從傳統的等級分化轉向現代的功能分化密切相關，並促使新型社會概念的出現。通過對比18世紀錢維城關於封建社會秩序的論述與20世紀初梁啟超對中國缺乏人口統計數據的反思，本文深入分析了社會功能分化與量化管理之間的關係。